Competencies and Skill Sets: A Prerequisite of Library Professionals in the New Normal - Lisa Sheba Rani, J.; Yesudoss, P. (Journal of Information and Knowledge, 2021)
COVID-19 has traumatized every area libraries are no exception. This article aims at suggesting how such challenges could be overcome by suitable competencies and skill sets in the new normal. Undoubtedly, the year 2020 witnessed the resilience of majority of library professionals and library associations as a community to support each other care and share the expertise. Now to look back, it is evident that the competencies and skill sets that have helped in organizing online events, virtual faculty development programs, webinars on various relevant topics have helped enormously to connect the users of the libraries. Based on the experience at Women’s Christian College (WCC) and Madras Christian College (MCC), competencies and skills sets that need to be a prerequisite to every library professional to meet the users’ needs in the era of new normal have been suggested.